2019
DOI: 10.1128/aem.02116-18
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis Wall Teichoic Acids Are Required for Biofilm Formation and Root Colonization

Abstract: Rhizosphere colonization by plant growth-promoting rhizobacteria (PGPR) along plant roots facilitates the ability of PGPR to promote plant growth and health. Thus, an understanding of the molecular mechanisms of the root colonization process by plant-beneficial Bacillus strains is essential for the use of these strains in agriculture. Here, we observed that an sfp gene mutant of the plant growth-promoting rhizobacterium Bacillus velezensis SQR9 was unable to form normal biofilm architecture, and differential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…In fact, two clusters containing polysaccharide biosynthesis genes were found ( Table S11 ). In addition, several genes involved in the production of teichoic acids, which play a role in biofilm formation and root colonization [59] were also identified ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, two clusters containing polysaccharide biosynthesis genes were found ( Table S11 ). In addition, several genes involved in the production of teichoic acids, which play a role in biofilm formation and root colonization [59] were also identified ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…For many bacteria, such as Bacillus amyloliquefaciens, Enterococcus faecalis, and Vibrio fischeri, the successful colonization of a host is influenced by their ability to attach and form a biofilm (Yaryura et al, 2008;Tischler et al, 2018;Xu et al, 2018;Willett et al, 2019). For P. syringae pv.…”
Section: The Role Of Calcium On Colonization Of S Rostratamentioning
confidence: 99%
“…A. caulinodans cannot only fix atmospheric nitrogen with S. rostrata in a symbiotic state ( Dreyfus and Dommergues, 1981 ), but also can fix nitrogen in a free-living state ( Dreyfus et al, 1983 ) or in association with non-legume plants, such as rice and wheat ( Liu et al, 2017a ). During the establishment of rhizobia-plant associations, biofilm formation on plant surfaces plays an important role ( Yaryura et al, 2008 ; Xu et al, 2018 ). However, the process of biofilm formation of A. caulinodans and the role of biofilm formation on its early symbiosis with S. rostrata are less studied.…”
Section: Introductionmentioning
confidence: 99%
“…to poor colonizer P. fluorescens strain WCS307 increased colonization of root tips [45]. Another study conducted by Xu et al [46] reported that wall teichoic acid (WTA) in B. velezensis SQR9 is crucial for root colonization and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%